UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION PADA SISWA KELAS VII B SMP TAMAN DEWASA IBU PAWIYATAN YOGYAKARTA - Meylisa Restu Indah Safitri (UNION: Jurnal Ilmiah Pendidikan Matematika, 2013)
The purpose of this research are to describe the process of implementation of the Integrated Cooperative learning models Reading and Composition (CIRC) to increase the activity and student chemistry learning outcomes in class VII B SMP Taman Dewasa Ibu Pawiyatan Yogyakarta. Type of research is action research class carried out in two cycles, where eachcycle consists of four stages, namely (1) planning, (2) implementating, (3) obserating,(4) reflecting. The subjects in this research are students of class VII B SMP Taman Dewasa Ibu PAwiyatan Yogyakarta, amounting to 19 students while the object in this research is the activity and student learning outcomes. Data obtained in this research include: student learning outcomesdrwan from the tes results at the end of cycle and the activity of students drawn from the observation sheets. The results showed an increase in every aspect of student activity proceeds as follows: aspects noted increased from 57.89% to 78.94%, aspects argues increased from 57,89% to 73,68%, aspects discuss increased from 60,52% to 55,26%, aspects do the problems increased from 55,26% to 86,84%, aspects respond to the teacher's instructions increased from 49,99% to 73,68% and aspects presentation increased from 36,84% to 65,78%. While the average math student learning outcomes increased from 61.05 in the first cycle to 72.10 in the second cycle.